1985
DOI: 10.1002/ijc.2910350517
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between tumour geometry and the response of tumour cells to cytotoxic drugs — An in vitro study using EMT6 multicellular spheroids

Abstract: Multicellular spheroids of the EMT6/Ca/VJAC mouse mammary tumour cell line have been used in an investigation of the effect of tumour geometry on the response of tumour cells to 3 cytotoxic drugs, adriamycin (ADM), nitrogen mustard (HN2) and CCNU. In addition to the inherent cellular drug response, factors related to spheroid structure, namely cell-cycle distribution, intercellular contact, drug penetration and microenvironment (pH, oxygen, glucose, etc.) are believed to influence the response of cells within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
32
0

Year Published

1987
1987
1998
1998

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 17 publications
12
32
0
Order By: Relevance
“…Both panels of Figure 1 show cellular radiosensitivity as a function of Hoechst staining intensity; in spheroids, the symmetry of the model allows an easy calculation of the depth from which the cells were recovered (Durand, 1983), while in the tumour system, the data are simply presented as fraction number, where fraction I represented the 10% of the cells which were most intensely stained (thus nearest the functional blood supply, e.g. Chaplin et al, 1985Chaplin et al, ,1986a (Figure 2) indicated that the less well oxygenated cells were more sensitive to this nitrosourea, in agreement with previous results obtained with nitrosoureas in other spheroid systems (Deen et al, 1980;Kwok & Twentyman, 1985). Quite reproducible responses were found in the multiple experiments shown (note that in the case of spheroids, different starting sizes led to slightly different estimates of cell depth among experiments).…”
Section: Resultssupporting
confidence: 84%
“…Both panels of Figure 1 show cellular radiosensitivity as a function of Hoechst staining intensity; in spheroids, the symmetry of the model allows an easy calculation of the depth from which the cells were recovered (Durand, 1983), while in the tumour system, the data are simply presented as fraction number, where fraction I represented the 10% of the cells which were most intensely stained (thus nearest the functional blood supply, e.g. Chaplin et al, 1985Chaplin et al, ,1986a (Figure 2) indicated that the less well oxygenated cells were more sensitive to this nitrosourea, in agreement with previous results obtained with nitrosoureas in other spheroid systems (Deen et al, 1980;Kwok & Twentyman, 1985). Quite reproducible responses were found in the multiple experiments shown (note that in the case of spheroids, different starting sizes led to slightly different estimates of cell depth among experiments).…”
Section: Resultssupporting
confidence: 84%
“…Similarly, cell proliferation-dependent uptake and cytotoxicity of melphalan have been described (Blosmanis et al, 1987). We have shown that nitrogen mustard is selectively toxic to exponential-phase LLTC cultures (Figure 4c), as previously reported for EMT6 cells (Twentyman & Bleehen, 1975;Kwok & Twentyman, 1985). In contrast chlorambucil, which probably enters cells passively (Goldenberg & Begleiter, 1980) is equally active against exponential and plateau-phase LLTC (Figure 4d).…”
Section: Discussionsupporting
confidence: 86%
“…The other intercalating agent studied, doxorubicin, also shows higher activity against exponential than against plateau-phase cultures (Figure 4b), as has been demonstrated with EMT6 (Twentyman & Bleehen, 1975;Kwok & Twentyman, 1985), CHO (Barranco & Novak, 1974), L1210 (Bhuyan et al, 1977) and LoVo (Drewinko et al, 1981) cells. Such cycle selectivity of intercalating drugs appears to reflect the activity of topoisomerase II, which declines in noncycling cells (Sullivan et al, 1986).…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations